Eksplorasi Work-Life Interface Karyawan Milenial pada Hotel Berbintang di Bali - I Gusti Ayu Putu Wita Indrayani (JURNAL BISNIS HOSPITALITI, 2022)
This study aims to identify and explore the perceptions of millennial employees regarding the intersection between personal life and work (work-life interface) during the COVID-19 pandemic. The dominance of millennial workers in the hotel industry in Bali is a challenge for hotel management to identify the factors that contribute to the intention to quit of  millennial employees through enriching the domains of personal and work life, which so far have not been widely studied. In-depth interviews with ten informants chosen using a purposive sampling method were used to collect data. The data analysis technique was carried out qualitatively. The data is then triangulated through several methods to meet the rules of qualitative research. The most significant finding in this study is that the work domain can enrich the personal lives of millennial employees. Through work context that is in accordance with the core values of the millennial generation, employees gain reinforcement to be able to carry out personal activities better. Work values can enrich the personal domain if employees have meaningful work, have positive support from the work environment, and if there are growth opportunities to develop their self-capacity.